Qualität statt Quantität verbessert die Weiterbildung - König, J.; Aeishen, S.; Cebulla, A.; Bellut, L.; Fassbach, M.; Westphal, J.; Struck, J. P. (Urologe, 2019)
Currently, continuing medical evaluation takes place in Germany—but not nationally or regularly, and without national standards. Therefore, comparisons between different clinics and trainers can currently not be drawn. Survey modes, such as those that have existed in Switzerland for decades, could provide a constructive basis in the assessment of the current continuing medical education of urology residents and subsequently facilitate the discussion on improvements. This requires constructive cooperation of all involved, without attributing the responsibility only to the educators. Models of rewarding good continuing education should also be found.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Development; Evaluation; Hospital; Resident; Urology